Application of the PBL Model Based on Deep Learning in Physical Education Classroom Integrating Production and Education. (18th February 2022) - Li, Honghai; Deng, Hongtao; Zhang, Yi
Abstract : This study aims to arouse students' interest in physical education (PE) in response to President Xi Jinping's call to strengthen students' physical quality because cultural courses occupy PE classes. Problem-based learning (PBL) is introduced, and a new teaching method of PE is proposed based on the convolutional neural network (CNN) in deep learning (DL). This method is employed to teach the experimental subjects in solid ball throwing. The students' interest, learning ability, and physical quality in the solid ball are investigated by a questionnaire survey. The questionnaire survey shows that the students' academic performance in solid ball throwing is improved, and their problem-solving ability, group cooperation ability, and theory learning ability are improved. Their time on a 1000-meter long run is shortened, and their body flexibility is improved. Therefore, it is believed that this new teaching method based on DL plays a significant role in improving students' physical quality.